Examining the effect of weight‐related recruitment information on participant characteristics: A randomized field experiment - Christy Wang; Jeffrey M. Hunger; Joseph Liao; David Figueroa; Alejandra Lopez; A. Janet Tomiyama (Wiley, 2024)
Abstract Objective Although 82% of American adults have a body mass index (BMI) of over 25, individuals with elevated BMI are considered difficult to recruit for studies. Effective participant identification and recruitment are crucial to minimize the likelihood of sampling bias. One understudied factor that could lead to sampling bias is the study information presented in recruitment materials. In the context of weight research, potential participants with higher weight may avoid studies that advertise weight‐related procedures. Thus, this study experimentally manipulated the phrasing of weight‐related information included in recruitment materials and examined its impact on participants' characteristics. Methods Two visually similar flyers, either weight‐salient or neutral, were randomly posted throughout a university campus to recruit participants (N = 300) for a short survey, assessing their internalized weight bias, anticipated and experienced stigmatizing experiences, eating habits, and general demographic characteristics. Results Although the weight‐salient (vs. neutral) flyer took 18.5 days longer to recruit the target sample size, there were no between flyer differences in respondents' internalized weight bias, anticipated/experienced weight stigma, disordered eating behaviors, BMI, or perceived weight. Absolute levels of these variables, however, were low overall. Conclusion Providing detailed information about study procedures allows participants to have more autonomy over their participation without differentially affecting participant characteristics.